Plant Nematology - Perry, Roland N; Moens, Maurice (Oxfordshire : C A B I, 2006)
Written by subject experts, this book provides an indispensible overview of all aspects of plant-parasitic nematodes. It begins by reviewing the basic structure and classification of nematodes, their taxonomy and phylogeny and the major groups of plant-parasitic nematodes. It moves on to cover their life cycle biology, the molecular characteristics of plant-nematode interaction and genetic engineering for resistance. The final section discusses quarantine legislation, sampling methods and management strategies including cultural schemes, the use of chemicals and resistant cultivars.
Includes References 411-431p.; Glossary 432-439p.; Index 440-447p.
Keywords: Nematode diseases of plants; Plant nematodes; Plant nematodes